The optimum light condition for Sutchi catfish larval rearing - Ismail, Khairul Muttaqin; Rosli, Muhammad Khairulanwar; Tan, Nai Han; Mohammad Noor, Normawaty; Mukai, Yukinori (2019)
Sutchi catfish Pangasianodon hypophthalmus (Sauvage, 1878) is one of the most important freshwater fish species cultured in Southeast Asia. Artificial seed production of sutchi catfish is very important in the aquaculture industry. However, the larval survival rates were low when reared in the hatchery. Providing optimum rearing condition for sutchi catfish larvae in the hatchery can increase the seeds production. The light condition was reported to influence the survival and growth of fish. Hence, this study was conducted to examine the optimum light condition in term of light wavelength and light intensity for sutchi catfish larval rearing. The sutchi catfish larvae were reared under five different light wavelengths (white, blue, green, yellow and red lights) and four different light intensities (1.40×10-4 , 1.40×10-3 , 1.40×10-2 , and 1.40×10-1 µmol/m²/s). The results showed that the survival rates (SR), growth rates (SGRTL and SGRBW) and production index (PI) were higher in red light than other wavelengths. For light intensity, only PI showed a significant effect on the larvae. Light intensity of 1.40×10-3 µmol/m²/s was significantly higher than 1.40×10-1 µmol/m²/s intensity. Apart from that, there was a tendency for high SR, SGRTL and SGRBW under low light intensities (1.40×10-4 and 1.40×10-3 µmoles/m²/s) when compared to high light intensities (1.40×10 -2 , and 1.40×10-1 µmol/m²/s). Therefore, red light wavelength and low light intensities (1.40×10 -4 and 1.40×10-3 µmoles/m²/s) were the optimum light condition for sutchi catfish larval rearing.